Biomass flows in an agro-pastoral village in West-Africa: Who benefits from crop residue mulching?. (February 2021) - Berre, D.; Diarisso, T.; Andrieu, N.; Le Page, C.; Corbeels, M.
Abstract: In West Africa, new management practices such as conservation agriculture with crop residue mulching can improve crop yields for individual farmers. However, in a context of complex social interactions between farmers, the introduction of such practices can also lead to conflicts between private interests and communal use of resources, for example the free grazing of crop residues. The objective of this paper was to assess ex-ante the impacts of the practice of crop residue mulching on crop productivity in a village of central Burkina Faso using an agent-based model, AMBAWA, that simulates the flows of biomass and nutrients between crop and livestock systems at the village scale. The model considers the interactions between four types of farmers that were identified in the study site: subsistence-oriented crop farmers, market-oriented crop farmers, agro-pastoralists and pastoralists. The model simulated increased cattle migration outside the village due to increased crop residue scarcity during the dry season with increased proportions of cropland under the practice of conservation agriculture, decreasing the manure availability at village scale. Consequently, the assumed direct yield increases due to soil moisture conservation as a result of mulching did not compensate for the yield losses resulting from lesser amounts of manure available. This effect was felt most strongly by farmers who own relatively large numbers of cattle (agro-pastoralists and pastoralists). The total maize production at village level depended more on the proportion of cropping land that was available for grazing by cattle, and thus not mulched, than on a possible direct effect of mulching on yield per se. The AMBAWA model can support discussion among stakeholders (farmers, traditional and administrative authorities) who are involved in the private and communal management of crop residues and other biomass resources, in order to co-design effective arrangements and practices for their sustainable use. Highlights: AMBAWA is an agent-based model that simulates biomass and nutrients flows. Biomass flows (manure, crop residue) were considered between four types of farmers. AMBAWA was used to assess the effect of crop residue mulching on crop productivity. Mulching decreased yields at village scale due to livestock migration (manure loss). Agent based models allows co-designing innovative practices in agro-pastoral areas.